Konsep Pendidikan Ubudiyah dalam Kitab Sullamut Taufiq Karya Syekh Abdullah bin Husain bin Thohir Ba Alawi - Karimah Karimah (Maharot : Journal of Islamic Education, 2020)
This article seeks to reveal the concept of ubudiyah education contained in the book Sullamut Taufiq Ila Mahabbatillah by Sheikh Abdullah bin Husain bin Thohir Ba Alawi which is one of the books that is widely recited, and studied in various institutions and Islamic boarding schools in Indonesia. To reveal this, the author uses literature search and review and other library materials that are relevant to the problem being studied, which includes materials contained in the book of Sullamut Taufiq as primary sources, and all writings related to ubudiyah education are secondary sources. While the data analysis technique that the author uses is content analysis which is used to draw conclusions through efforts to find the characteristics of the message, and multiply it objectively and systematically. After the data was collected, it was then analyzed using a descriptive data analysis method. The results of this research can be described: first, namely the concept of ubudiyah which includes; its meaning, kinds, principles, and objectives of ubudiyah itself. The second is ubudiyah education contained in the book of Sullamut Taufiq which includes matters that must be studied and carried out by every Muslim, such as prayer, fasting, zakat, hajj and so on.